Total growth and root-cluster production by legumes and proteas depends on rhizobacterial strain, host species and nitrogen level. - Lamont, Byron; Pérez-Fernández, M. (Oxford University Press, 2016)
BACKGROUND: Root clusters are bunches of hairy rootlets produced by >1800 species in nine families. The possible involvement of micro-organisms in root-cluster formation has produced conflicting results over the last 40 years. In addition, any effect of rhizobacteria on overall plant growth of root-cluster-bearing species remains unknown. AIMS: To evaluate the effect of seven rhizobacteria on total plant size, and relative cluster production, by three species, and relate outcomes to their indole-3-acetic acid (IAA)-producing ability as part explanation of past disparate results. METHODS: We grew Leucadendron salicifolium (from South Africa), Viminaria juncea (Australia) and Lupinus albus (Europe) in gnotobiotic, hydroponic culture at two nitrogen (N) levels and inoculated them with seven bacterial strains and harvested the plants after 13 weeks. KEY RESULTS: Following inoculation with all seven bacteria individually, plant growth sometimes greatly exceeded that of the aseptic controls, but, under other conditions, growth was less than the controls. Leucadendron and Lupinus failed to produce root clusters in the -N aseptic controls and Viminaria in the +N controls that was overcome by inoculating them with selected bacteria. Six bacteria were able to induce far more root clusters than those of the aseptic controls, while all bacteria sometimes suppressed cluster production in other treatments. All nine possible combinations of resource (plant size, indirect) and morphogenetic (relative cluster production, direct) effects were represented among the results, especially positive synergism (larger plants with a greater density of clusters). There was no clear relationship with IAA-producing ability of the seven bacteria, but low IAA strains of Pseudomonas putida and Bacillus magetarium were associated with greatest cluster production. CONCLUSIONS: While root-cluster formation can sometimes be induced by introducing rhizobacteria to aseptic culture, the growth-promoting properties of apparently beneficial bacteria on general growth and root-cluster production are best described as facultative, as their promotory effects depend on host species, growing conditions and index of plant response used.